Demographic, clinical and laboratory findings of severe and non-severe COVID-19 cases: one-year experience at a private set-up of Bangladesh (BIRDEM Medical Journal, 2022)
Background: COVID-19 has emerged in Dhaka city of Bangladesh since March 8, 2020 and rapidly spread throughout the country. Though non-severe cases can be managed in home, severe cases are more likely to be hospitalized and need intensive care unit (ICU) admission. Understanding the common demographic, clinical and laboratory features of severe versus non-severe patients could be quite useful for clinicians and might help to predict disease progression. This study aimed to compare demographic, clinical and laboratory findings among severe and non-severe COVID-19 cases.Methods: This retrospective study was conducted on confirmed COVID-19 patients who were admitted in a private set-up of Bangladesh, from 1st April 2020 to 31st March 2021. All confirmed COVID-19 cases were categorized into severe (severe/critical) and non-severe (asymptomatic/mild/moderate) group. The demographic, clinical and laboratory parameters were recorded. Patients’outcome was categorized by discharged (recovered), transferred to higher center (referred) and death.Results: Among 219 COVID-19 patients, 139 (78 males and 61 females) were in non-severe and 80 patients (56 males and 24 females) were in severe group. There was older age and male predominance among severe than nonsevere infection (pÂ0.05). The co-morbidities and smoking history showed non-significant differences between the groups. Among the presenting symptoms, cough and dyspnoea were present 91.3% and 61.3% respectively in severe vs 75.5% and 27.3% respectively in non-severe group. There was significantly lower percentages of lymphocyte (19.8 ± 12.6 %); higher values of ferritin (ng/mL) and D-dimer (mg/l) [1384.50 (103 - 2898) and 0.74 (0.03 - 883) respectively] among patients with severe COVID-19, pÂ0.05. On chest x-ray, pneumonitis was present in 69 (95.8%) patient in severe group, whereas 90 (78.3%) in non-severe group and the difference was statistically significant (pÂ0.05). High-resolution computed tomography (HRCT) scan of chest was done, in severe group 28 (80.0%) showed ground-glass opacity (GGO) and in non-severe group it was 41 (65.1%). The average duration of hospital stay was significantly higher in severe group (11.2 ± 8.1 days) than non-severe group (7.0 ± 5.9 days). Death was observed significantly higher in severe versus non-severe group (16.3% vs 1.4%) (p value